Patient Safety in Primary Care Socialization and Discussion - Dewi Mulfiyanti; Fitrah Ramadani; Andi Satriana; Andi Bintang (IJCS: International Journal of Community Service, 2022)
Patient safety has been recognized as an issue of global importance over the last 10 years. Unsafe primary and outpatient care results in greater morbidity, higher use of health services, and economic costs. All medical procedures against patients have their own risks. Of course, there is no single health worker or doctor who wants his patient to experience unwanted risks. Therefore, patient safety must be prioritized in every medical treatment by reporting Patient Accident Incidents (IKP), especially primary services or Public Health Center. Patient safety is an important key for every health facility. COMMUNITY SERVICE activities are carried out at UPT Public Health Center Bajoe Kel. Bajoe district. Tanete Riattang Timr Kab. Bones. Aims to explore the perception of Public Health Center officers on IKP and their reporting as well as increase knowledge about the types of IKP and their reporting. The results obtained from this Community Service are that the health officer understands the types of IKP and their reporting and understands the importance of policies and SOPs related to IKP reporting in primary health facilities such as Public Health Center.